Early Origins of Hypertension: Should Prevention Start Before Birth Using Natural Antioxidants? - Chien-Ning Hsu; You-Lin Tain (Antioxidants, 2020)
Hypertension may originate in early life. Reactive oxygen species (ROS) generated due to the exposure of adverse in utero conditions causes developmental programming of hypertension. These excessive ROS can be antagonized by molecules which are antioxidants. Prenatal use of natural antioxidants may reverse programming processes and prevent hypertension of developmental origin. In the current review, firstly we document data on the impact of oxidative stress in hypertension of developmental origin. This will be followed by effective natural antioxidants uses starting before birth to prevent hypertension of developmental origin in animal models. It will also discuss evidence for the common mechanisms underlying developmental hypertension and beneficial effects of natural antioxidant interventions used as reprogramming strategies. A better understanding of the reprogramming effects of natural antioxidants and their interactions with common mechanisms underlying developmental hypertension is essential. Therefore, pregnant mothers and their children can benefit from natural antioxidant supplementation during pregnancy in order to reduce their risk for hypertension later in life.